The trypanocidal effect of sesquiterpene lactones helenalin and mexicanin on cultured epimastigote - Jiménez Ortiz, Verónica (2005)
Sesquiterpene lactones constitute a large group of biologically active compounds obtained from plants. The lactones, mexicanin (MXN) and helenalin (HLN), were reported recently as active against the infective form of Trypanosoma cruzi. In this work, we studied the effects of these compounds on the growth and viability of the noninfective epimastigote, to compare the sensitivity of the 2 stages and to characterize their actions. Both compounds were cytotoxic to the parasites, with HLN (inhibitory concentration 50% [IC50] 1.9 +/- 0.08 microM) more potent than MXN (IC50 3.8 +/- 0.19 microM) and the typanocidal drug, benznidazole (IC50 8.6 +/- 2.5 microM). The results showed that epimastigotes are less sensitive than trypomastigotes to the compounds. The trypanocidal effect of these lactones, irreversible after 12-hr exposure, was not reversed by the reducing agents dithiotreitol or beta-mercaptoethanol. Ultrastructurally, we observed cytoplasmic vacuolization and nuclear disorganization. Although concentrations between 0.5 and 1.5 microM of the drugs were not lethal to the parasites, epimastigotes became thinner and their nuclei became more pycnotic after exposure. We conclude that MXN and HLN are deleterious for T. cruzi epimastigotes and that their mechanism of action is different than that of the related lactone, dehydroleucodine.